Comprehensive personalized ankle joint shape analysis of children with cerebral palsy from pediatric MRI - Cheng, Yue; Bailly, Rodolphe; Scavinner-Dorval, Claire; Fouquet, Benjamin; Borotikar, Bhushan; Ben Salem, Douraied; Brochard, Sylvain; Rousseau, François (Frontiers in Bioengineering and Biotechnology, 2022)
Cerebral palsy, a common physical disability in childhood, often causes abnormal patterns of movement and posture. To better understand the pathology and improve rehabilitation of patients, a comprehensive bone shape analysis approach is proposed in this article. First, a group analysis is performed on a clinical MRI dataset using two state-of-the-art shape analysis methods: ShapeWorks and a voxel-based method relying on ANTs registration. Second, an analysis of three bones of the ankle is done to provide a complete view of the ankle joint. Third, a bone shape analysis is carried out at subject level to highlight variability patterns for personnalized understanding of deformities.